Educational Media Of Ancient History Through Interactive, Evocative, And Interactive Display Design For Sangiran Museum Krikilan Cluster - Prasetyo Utomo, Tri; Hesti Heriwati, Sri; Laksani, Hening; Rahmat Ardi Candra Dwi Atmaja, Nur; Herry Prilosadoso, Basnendar; Nurhadi Panindias, Asmoro; Muslihah, Isnawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The Sangiran site is one of the most important prehistoric sites in the world, more than 50% of hominid fossils are found in this area and has extraordinary importance because it is considered a complete ecosystem laboratory consisting of geology, palaeontology, palaeobotany, and archaeology (ICOMOS, 1996). By UNESCO, the Sangiran Ancient Human Site was designated as a World Culture Heritage on 5 December 1996 in Merida (Mexico) by the World Heritage Committee with number C593, since then Sangiran has belonged to the world and has become one of three centres of ancient human evolution in addition to similar sites in Africa and China. Preservation of cultural knowledge through cultural knowledge by designing the Museum as a centre of information and cultural preservation. A museum through the exhibition system (museum display system) to convey information. The use of museum display facilities, tailored to the needs of the museum and the type of collection to be exhibited. The museum display system enables information communication. In the display system, objects are placed in displays with interpretations that can explain their meaning. The use of supporting facilities, also known as museum displays, is tailored to the needs and type of museum collection to be exhibited. To display a collection of artefacts about ancient human history, Sangran Museum Krikilan Cluster uses three presentation approaches: intellectual approach, romantic (evocative) approach, and interactive approach. The aim of this design is to determine an alternative display system in the exhibition space of the Sangiran Museum Krikilan Cluster to attract more visitors, both local and foreign.